Pengaruh Growth Mindset Terhadap Keterampilan Inovasi Siswa Teknik Pemesinan SMK ISLAM 1 BLITAR - Royani, Fahim; Nurhadi, Didik; Nurjanah, Nunung (Universitas Nahdlatul Ulama Blitar, 2025)
This survey aims to find out the influence of a growth mindset on the innovation skills of engineering students. This research uses quantitative research methods. The data analysis techniques used were inferential statistics, while the hypothesis testing techniques used were simple regression analysis techniques. Research instrument tests are tested with validity and reliability tests using SPSS for Windows applications. A simple regression prerequisite test consists of a normality test, a linearity test, and a Breusch-Pagan & White test. Then the result of the hypothesis test is that the regression coefficient is positive, so it can be said that the direction of the influence of the variable X on Y is positive. So the influence of a growth mindset on innovation skills has a significant influence value where the determination coefficient (R square) is 0.412, which contains the understanding that the impact of the free variable on the bound variable is 41.2%, and the value of F counts = 97.964 with the significance rate of 0.000 < 0.05, then it can be concluded there is an influence on the growth thinking variable over the innovation skill variable.